Companion shopping: the influence on mall brand experiences. Issue 4 (15th March 2019) - Merrilees, Bill; Miller, Dale
Abstract : Purpose: The purpose of this paper is to investigate the influence of a shopping companion on mall brand experience. Design/methodology/approach: The quantitative multi-group structural equation model study contrasts three shopper types: those shopping alone; those shopping with friends; and those shopping with family. Two categories are shoppers in a group. Nine hypotheses evaluate the impact of shopping with a companion. Findings: The results show that companions enhance the emotional brand experience. Further, shoppers with family companions are most able to enhance brand evaluation from mall brand experience. Shopping companions help co-create the shopping brand experience. Research limitations/implications: The findings are limited to Australian shoppers and contrast with Canadian studies, emphasizing friends. Alone shoppers place priority on price and only the alone shoppers are price-sensitive. The findings help address the gap in the literature, namely, understanding focal retail consumers in a group situation. Practical implications: Retailers and mall managers in planned shopping centers could consider developing different retail strategies and brand experiences, which address the specific types of customer groups or alone shoppers. Social implications: The paper is explicitly about social influences. Originality/value: This original research contributes new perspectives to understanding the role of companion shoppers as co-creators of the focal shopper's mall brand experience.